Information literacy for inquiry-based learning - Gasque, Kelley Cristine Gonçalves Dias (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
Given the importance of focus on globalized curriculum, this study presents a review of the literature on issues related to the nature of learning contents and curriculum, especially the development of curriculum based on the research process - inquirybased learning - in terms of information literacy. Some hypotheses were formulated to explain the lack of studies on this topic, such as the level of development of information literacy programs, pedagogical training of librarians, and educational institutions’ perceptions of the importance of information literacy. Recommendations for further research on the topic were made. It was concluded that inquiry-based learning allow better integration of information literacy content providing more meaningful learning by encouraging reflection, student protagonism, and learning how to learn among others. Palavras-chave: Curriculum. Information literacy. Learning contents. Projects method. Link: http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/2382/2334